RTHP-40. EFFECT OF RIND-BASED DOSIMETRIC TECHNIQUES FOR SCALP DOSE REDUCTION IN BRAIN IRRADIATION - No, Diana (Neuro Oncol, 2019)
OBJECTIVE: Radiation-induced alopecia is an unwanted side effect causing permanent cosmetic distress if hair regrowth does not occur. Rind-based techniques can effectively control dosimetric spread. We evaluated this technique to reduce scalp dose and alopecia while maintaining tumor coverage. METHODS: Ten consecutive brain tumor plans were retrospectively evaluated. All planning tumor volume (PTV) margins were ≤ 15.0mm from the skin surface. Departmental guidelines for fractionation were followed, with minimum 95% PTV coverage receiving 100% dose. Fractionation variation was accounted for with biologically effective dose calculation (alpha/beta=2). Rind structures encompassed 5mm depth from scalp surface; upper dose limits were customized to minimum values without PTV coverage compromise. Standard comparative plans using identical criteria, without rind structures, were calculated. Scalp dose evaluation was defined for tissue from skin to 5mm depth. Paired T-tests were used for comparative evaluation. RESULTS: Median age: 58 (range 27–85); 70% female (n=7). Histologies included gliomas (n=7) and meningiomas (n=3). Median PTV distance to skin surface: 13.5mm (range 8.0–15.0). Median PTV minimum and mean dose for rind-based plans: 88.63% (range 73.14–95.2) and 104.39% (range 102.07–107.38) of prescription and 90.90% (range 68.64–98.21) and 103.02% (range 101.91–107.04) for standard plans, respectively. Statistically significant reduction in scalp maximum and mean dose of 19.65% (p=2.72E(-06)) and 0.48% (p=0.007), respectively, was seen with rind-based planning. Scalp volume receiving 1000cGy-equivalent increased 6.7cc using rind-based techniques, although insignificant (p=0.33). Volume receiving 1500cGy-equivalent was significantly reduced 3.88cc (p=0.03) using rind-based techniques. With median 28.5 day follow-up, of 5 patients treated using rind-based techniques, 40% (n=2) exhibited acute alopecia compared to 100% of those treated with standard plans. CONCLUSION: Rind-based dosimetric techniques exhibit significant reduction of scalp dose in brain irradiation. 60% of patients treated using this technique experienced no alopecia, versus 0% receiving standard treatment. Further investigation is warranted to better evaluate correlation.